2003
DOI: 10.1038/sj.ejhg.5201076
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent triploidy of maternal origin

Abstract: Triploidy is the most frequent chromosome aberration in first trimester spontaneous abortions. In contrast to aneuploidies due to nondisjunction, increased maternal age is not a risk factor and the mechanism of triploidy remains poorly understood. To date, recurrence of triploidy of maternal origin has been described only in a few families suggesting some underlying genetic factors. Here, we report on a woman who underwent three consecutive triploid pregnancies, in two of which maternal origin of triploidy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 9 publications
0
21
0
2
Order By: Relevance
“…Its occurrence is not associated with an increase in maternal age, but whenever the additional chromosome complement is of paternal origin, the placenta exhibits histological characteristics of a partial hydatidiform mole (Brancati et al, 2003). In fact, in one of the cases with triploid karyotype, in which the anatomic-pathological study showed hydropic degeneration of the villi, we were able to demonstrate the paternal origin of the additional chromosome complement (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Its occurrence is not associated with an increase in maternal age, but whenever the additional chromosome complement is of paternal origin, the placenta exhibits histological characteristics of a partial hydatidiform mole (Brancati et al, 2003). In fact, in one of the cases with triploid karyotype, in which the anatomic-pathological study showed hydropic degeneration of the villi, we were able to demonstrate the paternal origin of the additional chromosome complement (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Maternal NLPR7 mutations were also involved in a few cases of diandric triploidies including 1 case of recurrent triploidy [Slim et al, 2011]. Recurrent digynic triploidy is more infrequent; to our knowledge, it has been reported in 5 cases [Pergament et al, 2000;BarAmi et al 2003;Brancati et al, 2003;Huang et al, 2004;Filges et al, 2015], although not in all triploid pregnancies a molecular investigation was performed. We are not aware of other cases with combination of a digynic triploidy and a zygotic tetraploidy with a PPMM contribution.…”
Section: Resultsmentioning
confidence: 76%
“…In this case, the phenotype is characterized by slight IUGR, and hypertrophic cystic placenta with partial hydatiform mola. The maternal triploidy is the result of digyny (fertilisation of a diploid oocyte by a normal sperm cell) and is characterized by severe asymmetric IUGR, with macrocephaly associated with hypoplasia of the other corporeal segments (4,(12)(13)(14)(15)(16). Other anomalies are common to the two forms of triploidy: anomalies of fingers (oligodactily and syndactily of fingers III and IV) different non-pathognomonic heart anomalies, genitourinary defects, lung anomalies and a non-specific facial dysmorphism (4,(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%